Challenges and Prospects of Technology Deployment for Elections in Nigeria under the Fourth Republic - Wahab, Shehu Layiwola (Kashere Journal of Politics and International Relations, 2024)
This paper explored the challenges and prospects of technology deployment for elections in Nigeria, using qualitative research design and the theory of social construction of technology as its theoretical foundation. The paper relied on semi-structured interviews with 12 purposively selected experts in technology deployment in the electoral process. Findings show that a number of challenges such as environmental factors, inadequate training for handlers of technologies during elections, the high cost of deploying technologies, corruption, and the vulnerability of technologies, etc. continue to beset the deployment of technologies for elections in Nigeria. The paper also found that technology has very good prospects to improve the electoral process in Nigeria; and that there is the need for the gradual introduction of more technologies in future elections in Nigeria. The paper made some recommendations for the need for INEC to deploy a monitoring mechanism for the technologies it deploys for elections; the gradual introduction of more technologies in the electoral process; and the need for political leaders, politicians and the INEC to develop the commitment and political will towards effective deployment of technologies for better elections in Nigeria.